2018
DOI: 10.1002/eap.1731
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sensitivity of seabed habitats to disturbance by bottom trawling based on the longevity of benthic fauna

Abstract: Bottom fishing such as trawling and dredging may pose serious risks to the seabed and benthic habitats, calling for a quantitative assessment method to evaluate the impact and guide management to develop mitigation measures. We provide a method to estimate the sensitivity of benthic habitats based on the longevity composition of the invertebrate community. We hypothesize that long‐lived species are more sensitive to trawling mortality due to their lower pace of life (i.e., slower growth, late maturation). We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 59 publications
(124 reference statements)
3
82
0
2
Order By: Relevance
“…A further extension of this research has shown that taxon longevity predicts recovery rate (Rijnsdorp et al 2018;Hiddink et al 2019). The latter finding concurs with expectations based on our understanding of the likely response of long-lived species.…”
Section: Quantification Of the Aggregated Effects Of Fishing Disturbasupporting
confidence: 90%
“…A further extension of this research has shown that taxon longevity predicts recovery rate (Rijnsdorp et al 2018;Hiddink et al 2019). The latter finding concurs with expectations based on our understanding of the likely response of long-lived species.…”
Section: Quantification Of the Aggregated Effects Of Fishing Disturbasupporting
confidence: 90%
“…This fraction is habitat‐specific and was derived by Rijnsdorp et al. () from the cumulative biomass distribution of infaunal invertebrates by T max category in the North Sea, as determined from grab and box core samples in untrawled locations (the effects of not including epifauna in these estimates is not known). Because we express category‐specific K as a fraction,K=ΣKj=1over T max categories j (although the approach could be based on absolute estimates of category‐specific K if they were available).…”
Section: Methodsmentioning
confidence: 99%
“…morphological, demographic or physiological attributes; Violle et al 2007), rather than their taxonomic identity, determine their responses to the environment (Keddy 1992, Diaz et al 1998). For example, community traits of benthic invertebrates are often scrutinized to investigate the impacts of bottom trawling, with species characterized by long lifespan or epifaunal position being less abundant in highly disturbed communities (De Juan et al 2007, Rijnsdorp et al 2018. For example, community traits of benthic invertebrates are often scrutinized to investigate the impacts of bottom trawling, with species characterized by long lifespan or epifaunal position being less abundant in highly disturbed communities (De Juan et al 2007, Rijnsdorp et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the use of traits provides a more mechanistic approach to understanding changes in community composition in comparison to more case-specific taxonomic information (McGill et al 2006, Shipley et al 2006. For example, community traits of benthic invertebrates are often scrutinized to investigate the impacts of bottom trawling, with species characterized by long lifespan or epifaunal position being less abundant in highly disturbed communities (De Juan et al 2007, Rijnsdorp et al 2018. Moreover, trait identity and diversity are linked to ecosystem functions (Diaz andCabido 2001, Gagic et al 2015) from which important ecosystem services can be derived, such as seafood and climate regulation.…”
Section: Introductionmentioning
confidence: 99%